1984
DOI: 10.1111/j.1442-9071.1984.tb01175.x
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Rigidity and Intraocular Pressure in Keratoconus

Abstract: EightyThe relative importance of corneal and scleral rigidity and of corneal thinning in the measurement of intraocular pressure is not clearly This study was planned to investigate a group of patients with keratoconus to determine which of these previously reported findings could be substantiated and to identify other possible factors which could be important in the routine clinical measurement of intraocular pressure in patients with low corneal rigidity or corneal thinning. MATERIALSEighty-five patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

1990
1990
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 14 publications
2
35
0
2
Order By: Relevance
“…Furthermore, that study found that corneal thinning was not the only factor, as IOP measurements were also reduced in patients with large sagging cones without corneal thinning. 10 We found no recently published data regarding to the possible influence of ectatic corneas on IOP readings obtained by DCT. Our study was conducted to compare IOP measurements by DCT with those by GAT in eyes with normal corneas and eyes with keratoconus.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Furthermore, that study found that corneal thinning was not the only factor, as IOP measurements were also reduced in patients with large sagging cones without corneal thinning. 10 We found no recently published data regarding to the possible influence of ectatic corneas on IOP readings obtained by DCT. Our study was conducted to compare IOP measurements by DCT with those by GAT in eyes with normal corneas and eyes with keratoconus.…”
Section: Introductionmentioning
confidence: 83%
“…Goldmann applanation tonometry measurements followed the guidelines from the Eye Care Technology Forum for standardizing the measurement of intraocular pressure for clinical research. 10 After the GAT readings, IOP was measured with DCT. The DCT is mounted on the slit-lamp similar to that used in the GAT readings and provides an absolute numerical output of IOP after coming in contact with the cornea for about 5 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] It has been inferred that keratoconus is an ectasia resulting from stromal stretching. 4,5 The term ectasia is defined as a dilation, expansion, or distension, all of which invoke the notion of an increase in surface area by a process of stretching. Despite wide acceptance that keratoconus represents a true ectasia, it has never been confirmed by objective measurements, nor have any accurate corneal surface area measurements been made from living corneas ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In keratoconus, high astigmatism, and stromal scarring, GAT may show greater variability and lower accuracy. [17][18][19] Brooks et al 18 found that GAT measurements yielded significantly lower values at the apex of the cone when compared to flatter or thicker areas of the cornea, which resulted in an overall underestimation of the true IOP. In keratoconus patients, GAT IOP seems to be 5.3±2.2 mmHg lower than that yielded by non-applanation tonometry, which seemed to provide measurements closer to the true IOP.…”
Section: Applanation Tonometers Goldmann Tonometer (Haag Streit Koenmentioning
confidence: 99%